2010
DOI: 10.1063/1.3442746
|View full text |Cite
|
Sign up to set email alerts
|

Matrix-free application of Hamiltonian operators in Coifman wavelet bases

Abstract: A means of evaluating the action of Hamiltonian operators on functions expanded in orthogonal compact support wavelet bases is developed, avoiding the direct construction and storage of operator matrices that complicate extension to coupled multidimensional quantum applications. Application of a potential energy operator is accomplished by simple multiplication of the two sets of expansion coefficients without any convolution. The errors of this coefficient product approximation are quantified and lead to use … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…In general, longer wavelets require greater computational effort and pose greater awkwardness in dealing with discontinuous boundaries. On the other hand, there may be applications where longer wavelets remain useful, e.g., applications based on projection using single-point quadrature for Coiflets [40] or generalized Coiflets [7] where the error order is at most M. For our applications, the arguments align solely in favor of using low-L basis functions. This minimizes the number of straddling functions at a boundary and minimizes the length of the multiscale recursions.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In general, longer wavelets require greater computational effort and pose greater awkwardness in dealing with discontinuous boundaries. On the other hand, there may be applications where longer wavelets remain useful, e.g., applications based on projection using single-point quadrature for Coiflets [40] or generalized Coiflets [7] where the error order is at most M. For our applications, the arguments align solely in favor of using low-L basis functions. This minimizes the number of straddling functions at a boundary and minimizes the length of the multiscale recursions.…”
Section: Discussionmentioning
confidence: 99%
“…Despite that common sentiment, Keinert and Kwon [5] and Neelov and Goedecker [6] demonstrated that one can beat this limit in reconstruction. Our group has recently generalized the latter results so that the reconstruction error can be tuned just as freely as the projection error [7]. There are particular consequences of this, as will be shown.…”
Section: Introductionmentioning
confidence: 89%
See 3 more Smart Citations